Impact of a 70 °C temperature on an ordinary Portland cement paste/claystone interface: An in situ experiment. (May 2016) - Lalan, Philippines; Dauzères, Alexandre; De Windt, Laurent; Bartier, Danièle; Sammaljärvi, Juuso; Barnichon, Jean-Dominique; Techer, Isabelle; Detilleux, Valéry
Abstract: Radioactive wastes in future underground disposal sites will induce a temperature increase at the interface between the cementitious materials and the host rock. To understand the evolution of Portland cement in this environment, an in situ specific device was developed in the Underground Research Laboratory in Tournemire (France). OPC cement paste was put into contact with clayey rock under water-saturated conditions at 70 °C. The initial temperature increase led to ettringite dissolution and siliceous katoite precipitation, without monosulfoaluminate formation. After 1 year of interaction, partial decalcification and diffuse carbonation (calcite precipitation) was observed over 800 μm in the cement paste. At the interface, a layer constituted of phillipsite (zeolite), tobermorite (well-crystallised C-S-H) and C-(A)-S-H had formed. Globally, porosity decreased at both sides of the interface. Geochemical modelling supports the experimental results, especially the coexistence of tobermorite and phillipsite at 70 °C, minerals never observed before in concrete/clay interface experiments.